Backtracking Indo-European languages influence on Indonesian - Purwitasari, Ana (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
Indo-European languages are the focus of this study which emphasized the influence of those languages on the Indonesian lexicon and linguistic diversity. In order to reach the goal of this work, diachronic and synchronic analysis were employed. Diachronic analysis referred to the theory of loanword form reconstruction stated by Mallory & Adams (2006) and borrowing process theory by Campbell (1998), while the synchronic analysis included loan type identification mentioned by Swe (2013). Consequently, the existence of Petjuk or Petjoh was identified as the diffusion of Dutch and Indonesian. There are also Portuguese family names which spread widely especially in East Indonesia and loanwords found. These loanwords are derived from mostly Germanic, while Indo-Iranian, Italic and Hellenic contributed also. Germanic languages, e.g. Dutch, German and English, and Portuguese as part of Italic supplied more loanwords for their long-lasting existence throughout the archipelago in the past during their colonization, while Indo-Iranian such as Sanskrit, Pali, Persian and Hindi gave their influence for coming into contact with Indonesians through trading activity. The only one Hellenic, e.g. Greek, and other Italic which are Latin and French became the donor through luxury loan for the need Indonesians acquire to translate some new terms which couldn’t be accommodated by Indonesian itself.